2015
DOI: 10.1242/jcs.156588
|View full text |Cite
|
Sign up to set email alerts
|

Focal adhesion kinase-related nonkinase (FRNK) negatively regulates IL-4-mediated inflammation

Abstract: Focal adhesion kinase (FAK)-related nonkinase (PTK2 isoform 6 in humans, hereafter referred to as FRNK) is a cytoskeletal regulatory protein that has recently been shown to dampen lung fibrosis, yet its role in inflammation is unknown. Here, we show for the first time that expression of FRNK negatively regulates IL-4-mediated inflammation in a human model of eosinophil recruitment. Mechanistically, FRNK blocks eosinophil accumulation, firm adhesion and transmigration by preventing transcription and protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…Further studies showed that either FAK siRNA or the dominant negative protein FAK‐related non‐kinase (FRNK) attenuated neutrophil transmigration across TNF‐α stimulated endothelial cells . Recently, we showed that FRNK also blocked eosinophil transmigration; however, the mechanism was different than what we found for neutrophils . In this case, FRNK acted independently of FAK and acted much earlier in the recruitment cascade by preventing the IL‐4‐induced expression of vascular cell adhesion molecule‐1 (VCAM‐1) and CCL26 …”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations
“…Further studies showed that either FAK siRNA or the dominant negative protein FAK‐related non‐kinase (FRNK) attenuated neutrophil transmigration across TNF‐α stimulated endothelial cells . Recently, we showed that FRNK also blocked eosinophil transmigration; however, the mechanism was different than what we found for neutrophils . In this case, FRNK acted independently of FAK and acted much earlier in the recruitment cascade by preventing the IL‐4‐induced expression of vascular cell adhesion molecule‐1 (VCAM‐1) and CCL26 …”
Section: Introductionmentioning
confidence: 57%
“…After 24 h, the incubation medium was removed and endothelial cell viability was measured using trypan blue exclusion. The supernatant was assayed for CCL26 using ELISA as previously described . The monolayer was then washed and endothelial cells were harvested for qPCR or Western blotting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been shown that IL-4 can enhance GATA6 expression at the level of transcription in human umbilical vein endothelial cells (Sharma et al, 2015). Therefore, we hypothesized that mTORC2 signaling was also regulating the expression of GATA6 at the level of mRNA.…”
Section: Resultsmentioning
confidence: 99%